Simulation study of sweetening and dehydration of natural gas stream using MEG solution - Alnili, Firas; Barifcani, Ahmed (Wiley-Blackwell Publishing, 2018)
© 2018 Canadian Society for Chemical Engineering. Natural gas is currently an important and popular fossil fuel and will likely continue to be in the future. In addition, natural gas can be considered as a source of hydrocarbon for petrochemical industries. Despite the fact that natural gas is mostly considered a "clean" fuel compared to other fossil fuels, the natural gas found in reservoir deposits is not necessarily "clean" and free of impurities. Natural gas consists primarily of methane, but it also contains considerable amounts of light and heavier hydrocarbons as well as contaminating compounds of CO 2 , N 2 , H 2 S, and other impurities. These impurities are undesirable compounds and cause several technical problems such as corrosion and environment pollution. However, many natural gas streams in different areas contain huge quantities of H 2 S and CO 2 . Many technologies can be used to purify the natural gas from acid gases. These technologies include Amine absorption, the adsorption process, cryogenic processes, and membranes. Therefore, this study aims to simulate the gas sweetening process by using the Aspen HYSYS V.7.3 program. Moreover, in this simulation work, MEG (Mono Ethylene Glycol) was selected as an absorbent for the gas sweetening process: it achieved high acid gas removal and reduced the water content from a stream of natural gas. In addition, the simulation work also achieved process optimization using several MEG concentrations and temperatures. It also investigated the effect of MEG concentrations and the inlet temperature of MEG on the regeneration reboiler temperature and duty.